Comparison of RLL, state diagram, grafcet and petri net for the realization of logic controller - Othman, Zulhairi (2005)
The strengths and weaknesses of popular pIc programming tools may be a common knowledge to the experienced but that contention alone lacks depth to the many others. Several studies have presented weighted comparisons but focused on only two approaches at a time. The first part of this paper presents qualitative comparisons among the 4 most popular approaches: relay ladder logic (RLL), state diagram, grafcet and ordinary Petri net. Each approach is weighted by their understandability, efficiency and flexibility. It is the intent of the second part of this study to formulate a mix and match LLD realization method based on the compared model strengths and weaknesses. The proposed model is then compared with the internationally accepted Grafcet approach in light of the same criteria as the first part. An analysis entails on what has been gained and lost in the proposed approach. From these comparisons ultimately, it is hoped that the pIc programmer is aware of the strengths and limitations of whichever programming approach chosen.